Study of glass-ceramic coating of dental implants in conditions of different bacterial status - Yanishen І. В.; Fedotova О. Л.; Savvova О. В.; Fesenko О. І.; Khlystun Н. Л.; Petrochenko Г. В. (Actual Dentistry, 2024)
Annotation. The ability of a surface to influence cell growth was known more than 100 years ago. Among the most commonly used functional coatings are bioactive glass ceramics, α/β TCP, tetracalcium phosphate, hydroxyapatite, zirconium, as well as growth factors, collagen, adhesive proteins, biologically active drugs, ions, and metals, including graphene. The purpose of the study was to improve the quality of orthopedic treatment of patients by studying the effect of glass-ceramic coating of dental implants in conditions of moderate and severe bacterial infection. Experimental samples were prepared in the form of discs with a thickness of 1 mm and a diameter of 10 mm. Glass crystal coating FAR-5.3- TZ is applied to a metal base made of titanium VT1-00 (slicker technology) and fired at a temperature of 780°С. The biotest inoculum was used to inoculate the MPB nutrient medium, into which a sample disk of FAR-5.3-TZ vitreous coating was placed. The study was conducted under conditions of moderate (initial bioassay density 103 cells/cm3) and severe (initial bioassay density 106 cells/cm3) bacterial infection. The prepared test tubes were placed in a thermostat for incubation at a temperature of 37 ± 1°C and kept for 6 and 24 hours. The study showed that during 6 hours of exposure, samples of glass crystal coating FAR-5.3-TZ were characterized by a bacteriostatic effect at biotest concentrations of 103 and 106 cl/cm3, which is manifested in a decrease in the formation of DHA by 1.8 and 1.2 times, respectively, which indicates their toxic effect in relation to E. coli culture. It was visually established that the intensity of the colored formazan in the control variants is greater than in the tested variants, which indicates an adequate reduction in the formation of DHA when the FAR-5.3-TZ glass-crystalline coating samples come into contact with the bioassay. Conclusions. The results of the study showed that the FAR-5.3-TZ vitreous coating sample, with an increase in the ratio of its contact area to the bioassay biomass density, suppresses metabolic processes in E. coli under the influence of the active substances of the vitreous coatings.